Dermatologic symptoms associated with gastrointestinal neoplasia - Beata Młynarczyk-Bonikowska; Jacek Muszyński; Sławomir Majewski (Termedia Publishing House, 2017)
Gastrointestinal tumors are among the most common neoplastic causes of death worldwide. Presence of characteristic skin lesions can allow faster diagnosis and therapy and this way can increase the probability of a cure. In the paper we present the most important paraneoplastic syndromes that can coexist with gastrointestinal malignancy including colon, gastric, esophagus and pancreatic cancers. We take into account genetic syndromes such as Cowden syndrome, familial atypical multiple mole melanoma syndrome (FAMMM) (melanoma/pancreatic cancer), Clarke Howel-Evans, Peutz-Jeghers, Muir-Torre, Gardner syndromes and acquired syndromes such as acantosis nigricans maligna, tripe palms, Leser-Trelat, Bazex, hypertrichosis languinosa, erythema gyratum repens , carcinoid and glucagonoma syndrome. We also include cutaneous metastases and coexistence of neoplasia in some cases of dermatomyositis.